Bilateral cavitary lung adenocarcinoma in a young lady: A rare case report with review of literature (Indian Journal of Case Reports, 2019)
A mucinous variant of bronchioloalveolar carcinoma is described as a rare variant of invasive adenocarcinoma and is characterized radiologically by consolidation, groundglass opacity, and nodules. Here, we report the case of a young lady with multiple cavitary disease presented with respiratory failure and mimicking as tuberculosis, pneumonia, vasculitis but initial laboratory investigations and bronchoscopy couldn’t clinch the diagnosis. Later on, CT-guided biopsy confirmed the diagnosis of mucinous bronchoalveolar carcinoma. Immunohistochemistry for TTF-1, EGFR, ALK, ROS mutation had been sent but the patient requested to discharge, have been put on EGFR inhibitor Gefitinib 250 mg once a day considering adenocarcinoma, female, Asian origin but couldn’t turn-up to review further details. The clinician should be aware of the cavitary presentation of adenocarcinoma of lung even in younger patients where the most common differential is tuberculosis.